2018
DOI: 10.1002/jemt.23069
|View full text |Cite
|
Sign up to set email alerts
|

EhRab21 mobilization during erythrophagocytosis in Entamoeba histolytica

Abstract: Rab proteins are present in all eukaryotic lineages and regulate vesicular trafficking. Entamoeba histolytica has approximately 100 genes encoding Rab proteins, among which 16 have homology with human Rab proteins. Human Rab21 participates in integrin recycling, and thus amoebic Rab21 was believed to regulate the mobilization of Ehβ1FNR (integrin‐like fibronectin receptor related with human integrin β1). We analyzed the distribution of EhRab21 using a polyclonal antibody produced with a specific peptide agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…E. histolytica genome sequencing revealed the presence of proteins usually located in the Golgi apparatus (Loftus et al, 2005). Recent studies using NBD‐6 ceramide, a specific Golgi marker, reported the participation of Rab21 in the trans‐Golgi network, by regulating vesicular transport towards the surface (Constantino‐Jonapa, Hernández‐Ramírez, Osorio‐Trujillo, & Talamás Rohana, 2018). However, in other studies the NBD‐6 ceramide has been used for tracking the behavior of Golgi apparatus (Javier‐Reyna et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…E. histolytica genome sequencing revealed the presence of proteins usually located in the Golgi apparatus (Loftus et al, 2005). Recent studies using NBD‐6 ceramide, a specific Golgi marker, reported the participation of Rab21 in the trans‐Golgi network, by regulating vesicular transport towards the surface (Constantino‐Jonapa, Hernández‐Ramírez, Osorio‐Trujillo, & Talamás Rohana, 2018). However, in other studies the NBD‐6 ceramide has been used for tracking the behavior of Golgi apparatus (Javier‐Reyna et al, 2012).…”
Section: Discussionmentioning
confidence: 99%